Bayesian network meta‐analysis comparing cryoablation, radiofrequency ablation, and antiarrhythmic drugs as initial therapies for atrial fibrillation. (11th December 2021) - Elsayed, Mahmoud; Abdelfattah, Omar M.; Sayed, Ahmed; Prasad, Rohan Madhu; Barakat, Amr F.; Elgendy, Islam Y.; Andrade, Jason; Jared Bunch, Thomas; Thosani, Amit; Saliba, Walid I.; Wazni, Oussama M.; Hussein, Ayman A.
Abstract: Background: Antiarrhythmic drugs (AADs) and catheter ablation are first line treatments of paroxysmal atrial fibrillation (PAF), however, there exists a paucity of data regarding the potential benefit of different catheter ablation technologies versus AADs as an early rhythm strategy. Objective: To assess the safety and efficacy of cryoablation versus radiofrequency ablation (RFA) versus AADs as a first line therapy of PAF. Methods: MEDLINE, Embase, Scopus and CENTRAL were searched to retrieve randomized clinical trials (RCTs) comparing cryoablation, RFA or AADs to one another as first line therapies for atrial fibrillation (AF). The primary outcome was overall freedom from arrhythmia recurrence (AF, atrial flutter [AFL], atrial tachycardia). Secondary outcomes included freedom from symptomatic arrhythmia recurrence, hospitalization, and serious adverse events. A random‐effects Bayesian network meta‐analysis was used to calculate odds ratios (OR) and 95% credible intervals (CrI). Results: Six RCTs ( N = 1212) met the inclusion criteria (605 AADs, 365 Cryoablation, and 245 RFA). Compared with AADs, overall recurrence was reduced with RFA (OR: 0.31; 95% CrI: 0.10–0.71) and cryoablation (OR: 0.39; 95% CrI: 0.16–1.00). Comparing ablation (cryoablation and RFA) with AADs in respect to freedom from symptomatic AF recurrence, neither cryoablation (OR: 0.35; 95% CrI: 0.06–1.96) nor RFA (OR: 0.34; 95% CrI: 0.07–1.27) resulted in statistically significant reductions individually compared to AADs, though pooled ablation with both technologies showed lower odds of arrhythmia recurrence (OR: 0.35; 95% CrI: 0.13–0.79). In terms of serious adverse events rates, neither cryoablation (OR: 0.77; 95% CrI: 0.44–1.39) nor RFA (OR: 1.45; 95% CrI: 0.67–3.23) were significantly different to AADs. RFA resulted in a statistically significant reduction in hospitalizations compared to AAD (OR: 0.08; 95% CrI: 0.01–0.99), whereas cryoablation did not (OR: 0.77; 95% CrI: 0.44–1.39). The surface under the cumulative ranking curve showed RFA to be the most effective treatment at reducing overall rates of recurrence, symptomatic recurrence and hospitalizations; whereas cryoablation was most likely to reduce serious adverse events. Conclusion: Cryoablation and RFA are both effective and safe first line therapies for AF compared to AADs, with RFA being the most effective at reducing recurrences. Condensed Abstract: Atrial fibrillation (AF) has been associated with significant morbidity and mortality. Early treatment of AF can decrease recurrences or arrhythmia burden; avoiding, as such, functional and economically debilitating consequences. In this network meta‐analysis, the safety and efficacy of cryoablation, radiofrequency ablation (RFA), and antiarrhythmic drugs (AAD) as initial treatments of paroxysmal AF were compared. The study shows that cryoablation and RFA, employed as the first‐line strategy for the treatment of AF, significantly reduce atrial tachyarrhythmia recurrences compared to AAD without increasing the risk of serious adverse events.